PENINGKATAN PEMAHAMAN KONSEP MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR MELALUI SMALL GROUP DISCUSSION - Utami, Putri; Ismaniati, Christina; Mustadi, Ali (Universitas Djuanda, 2019)
This research applied Small Group Discussion learning model to improve the understanding of concept of KKNI 6th level students to match their expert field. The observations showed that the concept understanding of students was still low. This research was a classroom action research with Kemmis McTaggart cycle model. This classroom action research was conducted over two cycles. Each cycle consisted of two meetings. The subjects of the research were 2A class students of the Elementary School Teacher Education Program in Yogyakarta State University which amounted to 39 students. The data collecting technique in this research was test, while the data analysis technique used descriptive quantitative by finding mean then described. The result of the research showed that the concept understanding of the students in pre-action condition were 55,2 included in low category, then the average of students’ understanding concept increased in the first cycle with score 64,7. In cycle II, the students’ understanding concept increased significantly with score 77,3. Based on the research, it can be concluded that the SGD model can improve the students' concept understanding.